2014
DOI: 10.3389/fncel.2014.00216
|View full text |Cite
|
Sign up to set email alerts
|

Role of mitochondria ROS generation in ethanol-induced NLRP3 inflammasome activation and cell death in astroglial cells

Abstract: Toll-like receptors (TLRs) and NOD-like receptors (NLRs) are innate immunity sensors that provide an early/effective response to pathogenic or injury conditions. We have reported that ethanol-induced TLR4 activation triggers signaling inflammatory responses in glial cells, causing neuroinflammation and brain damage. However, it is uncertain if ethanol is able to activate NLRs/inflammasome in astroglial cells, which is the mechanism of activation, and whether there is crosstalk between both immune sensors in gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
163
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 228 publications
(172 citation statements)
references
References 59 publications
5
163
1
3
Order By: Relevance
“…It is also interesting that the most robust changes observed in the different cell lines consistently came from LonP1, which specifically recognizes oxidized proteins and targets them for degradation (35). Compromising homeostasis of the mitochondrion can lead to apoptosis, and one of the primary downstream effectors of the mtUPR in immune cells is activation on the inflammasome (22,38,41,42). This was prevented in cells lacking FABP4/aP2, as observed from the decrease in mRNA and protein levels of the inflammasome members, as well as its activation (IL-1␤ secretion).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also interesting that the most robust changes observed in the different cell lines consistently came from LonP1, which specifically recognizes oxidized proteins and targets them for degradation (35). Compromising homeostasis of the mitochondrion can lead to apoptosis, and one of the primary downstream effectors of the mtUPR in immune cells is activation on the inflammasome (22,38,41,42). This was prevented in cells lacking FABP4/aP2, as observed from the decrease in mRNA and protein levels of the inflammasome members, as well as its activation (IL-1␤ secretion).…”
Section: Discussionmentioning
confidence: 99%
“…The bioactive form of IL-1␤ must be generated by inflammasome-dependent cleavage and secretion, which can be triggered by ROS (as well as other sources) through the mitochondrial intrinsic apoptotic pathway (22,38). To assess activation of the inflammasome in the FABP4/aP2 system, IL-1␤ secretion was evaluated in response to either pharmacologic or genetic ablation of FABP4/aP2.…”
Section: ) As Shown Inmentioning
confidence: 99%
“…Some studies have identified the specific inflammatory mediators released in response to ethanol. For example, acute ethanol treatment of cultured astrocytes causes upregulation of iNOS and COX-2 [56], and chronic ethanol activates the NLRP3 inflammasome in astrocytes from cerebral cortex and in primary cultures of astrocytes [93]. Ethanol also promotes TLR4 signaling in astrocytes and microglia, which leads to upregulation of inflammatory cytokines, including IL-1β, TNF-α, IL-6, iNOS and COX-2 [63].…”
Section: Alcohol-exposed Astrocytes As Immune Regulatorsmentioning
confidence: 99%
“…However, other studies disagree with these findings and suggest NLRP3 activation in astrocytes after CNS injury. Therefore, further studies are needed to address these issues [43,44].…”
Section: Nlrp3 Pathway As a Target For Ad Treatmentmentioning
confidence: 99%